A Visual-Analogue Screening Tool for Assessing Mood and Quality of Daily Life Complications in Family Members of People Living With Cancer: Portuguese Version of the Emotion Thermometers: Burden Version. Issue 4 (December 2020) - Areia, Neide P.; Mitchell, Alex; Fonseca, Gabriela; Major, Sofia; Relvas, Ana P.
Cancer is a disease that impacts not only the patient but also affects the entire family. Family members experience high levels of distress. Therefore, screening for cancer-specific distress among family members of people with cancer is important but relatively unexplored. This cross-sectional study aims to analyze the psychometric properties of a screening tool for family members of people with cancer. We examined the usefulness of the emotional thermometers burden version (ET-BV) in detecting caregiver emotional distress. The ET-BV is a simple multidomain visual analogue scale distributed in two major domains: "emotional upset" and "impact." A total of 364 cancer patients' family members completed the ET-BV and Brief Symptom Inventory. Analyses were aimed to examine the diagnostic accuracy (receiver operating characteristic) of the ET-BV. A fair to good diagnostic accuracy was achieved for ET-BV. For emotional upset thermometers, a cutoff of ≥5 was determined and for impact thermometers, a cutoff of ≥4 was established. ET-BV seems to be a useful, quick, and simple tool for distress screening in family members of people with cancer. A revision of a specific thermometer is discussed in order to increase ET screening performance and clinical utility.